Sex difference in the relationship between 24-h sodium–potassium ratio and prevalence of metabolic syndromes: a cross-sectional study - Li Wang; Yuyang Xiao; Rubing Guo; Ying Li; Lu Yin; Zhangchi Yuan; Pingting Yang; Xue He; Shanhu Yao; Yuexiang Qin; Jihong Hu (Scientific Reports)
Abstract Maintaining a balanced ratio between sodium and potassium intake is one of the most important dietary and lifestyle factors in the development of metabolic syndrome (MetS), but available evidence is still limited, particularly when using urine samples to estimate this ratio. We aim to evaluate the associations between the 24-h urinary sodium–potassium ratio (24hUNa/KE) and MetS risk through a large health check-up program in China. This cross-sectional study analyzed health check-up data from 59,292 participants at the Third Xiangya Hospital’s Department of Health Management in Changsha, China, from 2018 to 2021. Each participant gave one fasting urine sample to analyze sodium, potassium, and creatinine levels during the check-up. The Kawasaki formula estimated 24-h urinary sodium (24hUNaE) and potassium excretion (24hUKE), with the 24hUNa/KE ratio calculated by dividing 24hUNaE by 24hUKE. The prevalence of MetS was found to be 19.27%. Notably, the overall MetS prevalence was higher in men (28.08%) than in women (7.83%). In women, MetS prevalence increased from 6.35 to 10.30% across the lowest to highest 24hUNa/KE quartiles. A significant increase in MetS prevalence was associated with each standard deviation increase in 24hUNa/KE (adjusted odds ratio [AOR], 1.03; 95% confidence interval [CI] 1.01–1.06), particularly for central obesity (AOR, 1.04; 95% CI 1.02–1.06) and elevated blood pressure (AOR, 1.20; 95% CI 1.17–1.22). In women, a one standard deviation increase in the 24hUNa/KE ratio raised the risk of MetS by 9% (AOR, 1.09; 95% CI 1.05–1.14), but no significant link was found in men. A strong positive link exists between 24hUNa/KE and MetS and its components, especially central obesity and high blood pressure, with a more significant effect in women.